Dinaciclib as an effective pan-cyclin dependent kinase inhibitor in platinum resistant ovarian cancer - Howard, David; James, David; Garcia-Parra, Jezabel; Pan-Castillo, Belen; Worthington, Jenny; Williams, Nicole; Coombes, Zoe; Rees, Sophie Colleen; Lutchman-Singh, Kerryn; Francis, Lewis W.; Rees, Paul; Margarit, Lavinia; et al. (Frontiers in Oncology, 2022)
Background: Ovarian cancer (OC) is amongst the most lethal of common cancers in women. Lack of specific symptoms in the early stages, OC is predominantly diagnosed late when the disease has undergone metastatic spread and chemotherapy is relied on to prolong life. Platinum-based therapies are preferred and although many tumors respond initially, the emergence of platinum-resistance occurs in the majority of cases after which prognosis is very poor. Upregulation of DNA damage pathways is a common feature of platinum resistance in OC with cyclin dependent kinases (CDKs) serving as key regulators of this process and suggesting that CDK inhibitors (CDKis) could be effective tools in the treatment of platinum resistant OC. Aim: The aim of this study was to evaluate the efficacy of CDKis in platinum resistant OC models and serve as a predictor of potential clinical utility. Methods: The efficacy of CDKi, dinaciclib, was determined in wildtype and platinum resistant cell line pairs representing different OC subtypes. In addition, dinaciclib was evaluated in primary cells isolated from platinum-sensitive and platinum-resistant tumors to increase the clinical relevance of the study. Results and Conclusions: Dinaciclib proved highly efficacious in OC cell lines and primary cells, which were over a thousand-fold more sensitive to the CDKi than to cisplatin. Furthermore, cisplatin resistance in these cells did not influence sensitivity to dinaciclib and the two drugs combined additively in both platinum-sensitive and platinum-resistant OC cells suggesting a potential role for pan-CDKis (CDKis targeting multiple CDKs), such as dinaciclib, in the treatment of advanced and platinum-resistant OC.